2013
DOI: 10.12691/ces-1-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Milnacipran by Simple Colorimetric Methods

Abstract: In the present study, two sensitive, precise and accurate spectrophotometric methods have been developed for the determination of milnacipran in bulk and capsule formulation. The first method is based on the reaction of milnacipran with ninhydrin in N,N'-dimethylformamide medium at 80°C temperature to form a colored Ruhemann's purple, which exhibits absorption maximum at 575nm. The second method is based on extraction of milnacipran into chloroform as ion-pair with bromothymol blue. The yellow colored ion-pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…MCN is a norepinephrine and serotonin reuptake inhibitor, for cure of depression and fibromyalgia [2]. Several analytical assays were described for the detection of selected drug such as spectrophotometric [4][5][6][7][8], Spectrofluorimetric [9,10], HPLC [11,12], HPTLC [15][16][17]. From the reported methods we found that there is a method has been described for determination of MCN which depends on measurement of the absorbance of cited drug solution at the cutoff point of many solvents 220 nm, which limits the methods selectivity [18].…”
Section: Introductionmentioning
confidence: 99%
“…MCN is a norepinephrine and serotonin reuptake inhibitor, for cure of depression and fibromyalgia [2]. Several analytical assays were described for the detection of selected drug such as spectrophotometric [4][5][6][7][8], Spectrofluorimetric [9,10], HPLC [11,12], HPTLC [15][16][17]. From the reported methods we found that there is a method has been described for determination of MCN which depends on measurement of the absorbance of cited drug solution at the cutoff point of many solvents 220 nm, which limits the methods selectivity [18].…”
Section: Introductionmentioning
confidence: 99%
“…4 It acts by unique and equal inhibition of noradrenaline and serotonin neurotransmitters reuptake. 5 In the previous analytical literature, MLC was assayed by various techniques which include GC-MS, 6 liquid chromatography with uorescence or UV detection, 7,8 spectrouorimetry by derivatization with ninhydrin 9 or NBD-Cl, 10 UVspectrophotometric detection at 223 nm 11,12 and colorimetry using ninhydrin 13 or ion pair complex. 14 The approach target was simple development for accurate assay of MLC in the spiked biological uid, and tablets.…”
Section: Introductionmentioning
confidence: 99%
“…14 The approach target was simple development for accurate assay of MLC in the spiked biological uid, and tablets. The method provides advantages over the published method as the heating step is absent which make the method is more facile than the reported methods, 9,10 non-extractive, 13,14 low LOD and LOQ, 9,11,13,14 and nally implemented in non-sophisticated and easily available equipment.…”
Section: Introductionmentioning
confidence: 99%